PET of Insulinoma using (18)F-FBEM-EM3106B, a New GLP-1 Analog - Gao, Haokao (2011)
Derived from endocrine pancreatic beta cells, insulinomas express glucagon-like peptide-1 (GLP-1) receptor with high density and incidence. In this study, we labeled a novel GLP-1 analog, EM3106B, with (18)F and performed PET imaging to visualize insulinoma tumors in an animal model. A GLP-1 analog that contains multiple lactam bridges, EM3106B, was labeled with (18)F through a maleimide-based prosthetic group, N-2-(4-(18)F-fluorobenzamido) ethylmaleimide ((18)F-FBEM). The newly developed radiotracer was characterized by cell based receptor-binding assay, cell uptake and efflux assay. The stability in serum was evaluated by radio-HPLC analysis. In vivo PET imaging was performed in nude mice bearing subcutaneous INS-1 insulinoma tumors and MDA-MB-435 tumors of melanoma origin. Ex vivo biodistribution study was performed to confirm the PET imaging data. EM3106B showed high binding affinity (IC(50) = 1.38 nM) and high cell uptake (5.25 ± 0.61% after 120 min incubation). (18)F-FBEM conjugation of EM3106B resulted in high labeling yield (24.9 ± 2.4%) and high specific activity (>75 GBq/ μmol at the end of bombardment). EM3106B specifically bound and was internalized by GLP-1R positive INS-1 cells. After intravenous injection of 3.7 MBq (100 μCi) of (18)F-FBEM-EM3106B, the INS-1 tumors were clearly visible with high contrast in relation to the contralateral background on PET images, and tumor uptake of (18)F-FBEM-EM3106B was determined to be 28.5 ± 4.7 and 25.4 ± 4.1 %ID/g at 60 and 120 min, respectively. (18)F-FBEM-EM3106B showed low uptake in MB-MDA-435 tumors with low level of GLP-1R expression. Direct tissue sampling biodistribution experiment confirmed high tracer uptake in INS-1 tumors and receptor specificity in both INS-1 tumor and pancreas. In conclusion, (18)F-FBEM-EM3106B exhibited GLP-1R-receptor-specific targeting properties in insulinomas. The favorable characteristics of (18)F-FBEM-EM3106B, such as high specific activity and high tumor uptake, and high tumor to non-target uptake, demonstrate that it is a promising tracer for clinical insulinoma imaging.